Plasticity of preferred body temperatures as means of coping with climate change? - Gvozdík, Lumír (Biology letters, 2012)
Thermoregulatory behaviour represents an important component of ectotherm non-genetic adaptive capacity that mitigates the impact of ongoing climate change. The buffering role of behavioural thermoregulation has been attributed solely to the ability to maintain near optimal body temperature for sufficiently extended periods under altered thermal conditions. The widespread occurrence of plastic modification of target temperatures that an ectotherm aims to achieve (preferred body temperatures) has been largely overlooked. I argue that plasticity of target temperatures may significantly contribute to an ectotherm's adaptive capacity. Its contribution to population persistence depends on both the effectiveness of acute thermoregulatory adjustments (reactivity) in buffering selection pressures in a changing thermal environment, and the total costs of thermoregulation (i.e. reactivity and plasticity) in a given environment. The direction and magnitude of plastic shifts in preferred body temperatures can be incorporated into mechanistic models, to improve predictions of the impact of global climate change on ectotherm populations.
Keywords: Environment; Behavior, Animal; Selection, Genetic; chování zvířat; klimatické změny; Body Temperature Regulation; Temperature; selekce (genetika); Climate Change; životní prostředí; termoregulace; teplota; Animals; zvířata; aklimatizace; Acclimatization